(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The point of this paper is to demonstrate, basically, three normal fixed point hypotheses for six self mappings of a Menger space utilizing two feebly viable sets having CLRJCLR-property and fulfilling a certain connection. These sum up a few realized outcomes including those of Kohli et. al.